Establishing patterns of nitrogen application for fire safety of sunflower grain storage facilities - Tsapko, Yuriy; Sokolenko, Kostiantyn; Vasylyshyn, Roman; Melnyk, Oleksandr; Tsapko, Аleksii; Bondarenko, Olga; Karpuk, Anatolii (Eastern-European Journal of Enterprise Technologies, 2022)
The issue of using nitrogen to eliminate fires in granaries is related to ventilating the grain mass with nitrogen while it is necessary to take into consideration the change in gas concentration. Therefore, the object of this research was the value of the minimum concentration of nitrogen to eliminate the combustion of sunflower grain. It has been proven that in the process of thermal destruction of sunflower grain, the composition of gaseous products of thermal destruction of sunflower grain contains more than 70 % of combustible gases. Namely: carbon monoxide, over 51 %; hydrogen, about 5.7 %; and hydrocarbons with a total concentration of 13.72 %, which provide fire hazardous properties of organic material. Therefore, it should be noted that the release of the amount of combustible gases during pyrolysis requires a reduction in the amount of oxygen in the gas-air environment to eliminate fire sites. Obviously, such a mechanism for the decomposition of sunflower grain during pyrolysis is a factor in regulating the extinguishing process, due to which the amount of nitrogen to eliminate combustion increases. Comparison of experimental studies on the composition of gaseous products of thermal destruction of sunflower grain and studies to determine the minimum fire extinguishing concentration of nitrogen, at which combustion was stopped, made it possible to justify the use of nitrogen. Based on the study's results on the elimination with nitrogen of fire sites of sunflower grain, the values of the minimum fire extinguishing concentration were revealed at extinguishing, about 33.7 % by volume. At the same time, terminating the combustion of sunflower grain occurs with a decrease in the concentration of oxygen in the gas-air environment of about 14 %. The practical significance is the fact that the results obtained for determining the minimum fire extinguishing concentration of nitrogen make it possible to establish operating conditions for granaries when eliminating fire sites